BIOLOGI REPRODUKSI IKAN BETOK (Anabas testudineus Bloch, 1792) DI RAWA BANJIRAN SUNGAI MAHAKAM, KALIMANTAN TIMUR [Reproductive biology of climbing perch (Anabas testudineus Bloch, 1792) in floodplain of Mahakam River, East Kalimantan] - Yunizar Emawati; M. Mukhlis Kamal; Noncy Ayu Yolanda Pellokila (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2009)
A study that head for to find out some aspects biology reproduction of climbing perch (Anabas testudineus) in floodplains of Mahakam River, East Kalimantan that have been conducted of November until January with survey method. Floodplain in the Mahakam River is one of area freshwater fishing which plays an important role for East Kalimantan’s societies. Results research suggested that classified water quality from Mahakam’s drainage basin floodplain as still be able to support of climbing perch life. Climbing perch has growth patterns as a whole is negative allometric (b<3). Most Climbing perch are caught are fish had entered the GMR 3 and 4 (gonado maturity). Climbing perch classified potentially high reproduction because it has a large fecundity.